Pragmatism as a Theoretical Source of E. Nagel’s Philosophy - Petkevičiūtė, Nijolė (Problemos, 1986)
The article considers the impact of the ideas of pragmatism in the origination of American philosophy of science, and particularly in the origination of E. Nagel’s conception of science. The latter has appropriated to some extent the doctrine of fallibilism, the critical attitude towards the role of common sense in scientific knowledge, Ch. Peirce’s idea of necessary link between the rational and the sensible, and J. Dewey’s instrumentalism. The ideas of pragmatism are critically analysed, the evolution of the pragmatic maxim in the philosophical development of Ch. Peirce is cleared up and the sense in which the maxim was used by E. Nagel is revealed. The conclusion is drawn that namely under the influence of pragmatic school E. Nagel has explained science as a self-correcting process and has solved the problem of demarcation of science not in the reductionist manner of neopositivism, but by the way of explication of scientific method.